EKSISTENSI PASAR-PASAR TRADISIONAL DI KOTA SEMARANG TAHUN 1873 – 1914 (Forum Ilmu Sosial, 2009)
Since 1873 can be regarded as the beginning of growth and development of traditional marketsignifi cantly in Semarang. The deadline was set in 1914, based on the 30 April 1914 Besluit No.379 ofdecentralized market businesses submitted to the local council (city council). Above conditions, led toproblems including: the form of regulation, market management and the government’s revitalization ofthe markets in Semarang. Since decentralization, the delegation obtained Semarang Municipal obligationsin managing public facilities including care and repair and even build a set of market infrastructure. Untilthe year 1910 the market management in Semarang are still under the direct supervision of the colonialgovernment. Revitalization evidenced by an increase in the quality and infrastructure through discussion atcity council level. Various efforts related to the revitalization of the market almost all the elements to giveher attention. Technical Committee started, City Project Director, Chairman of the City Council, Memberof the Council, the Commission indicates the involvement of all markets is intense. Revitalization of thewhole market began to be realized from the building and management system. Not just action for theorder, cleanliness, security, cleanliness, health, but the administration and supervision of fi nancial marketsmeans the attention of many parties. Order of the occupation has given a lot of positive infl uence in thedevelopment of markets empowerment in Semarang and of course can be used as a source of learning.Irrespective of political background surrounding the economic-colonialist interests.Key words: Eksistention, traditional market, decentralization.